2020
DOI: 10.1166/jbn.2020.2871
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Based Nanoparticles Can Overcome the Radioresistance of Head and Neck Squamous Cell Carcinoma Through the Induction of Autophagy

Abstract: Radiation therapy is a mainstay in the therapeutic management of Head and Neck Squamous Cell Carcinoma (HNSCC). Despite significant progress in this field, radioresistance still accounts for most treatment failures. Gadolinium-based nanoparticles (GBNs) have shown great promises as radiosensitizers but the underlying sensitizing mechanism is still largely unknown with regards to the disparities obtained in in vitro studies. In this study, we show that a new formulation of GBNs, AGuIX®, can radiosensitize HNSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…NPs based on rare-earth elements—including those of gadolinium, cerium, neodymium—have been reported to induce autophagy in human macrophage THP-1 cells [ 63 ], in two human glioblastoma cells ( U -87 MG and Mo59 K) [ 64 ] and in the cells of head and neck squamous cell carcinoma (HNSCC) [ 65 ]. Recently, gadolinium compound has also been reported to induce autophagy in the Mediterranean mussel Mytilus galloprovincialis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPs based on rare-earth elements—including those of gadolinium, cerium, neodymium—have been reported to induce autophagy in human macrophage THP-1 cells [ 63 ], in two human glioblastoma cells ( U -87 MG and Mo59 K) [ 64 ] and in the cells of head and neck squamous cell carcinoma (HNSCC) [ 65 ]. Recently, gadolinium compound has also been reported to induce autophagy in the Mediterranean mussel Mytilus galloprovincialis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in radioresistant head and neck squamous cell carcinoma (HNSCC) SQ20B cells aimed to understand the radiosensitizing mechanisms in presence of AGuIX NPs. 61 Using 250 kV X-Rays, a surviving fraction at 4 Gy of 1.382 was obtained with an enhanced biological factor of 1.3 (incubation of cells at 0.8 mM in gadolinium). According to a previous study on U87MG glioblastoma cells, 58 AGuIX NPs are shown to principally localize in lysosomes with no particles detected in the nucleus.…”
Section: Radiosensitizationmentioning
confidence: 99%
“…It is a nonapoptotic form of programmed cell death caused by overactivated autophagy (Booth et al, 2019;Zhu et al, 2020). Anticancer treatment induces robust autophagy of cancer cells to self-digestion until death (Simonet et al, 2020;Ganesher et al, 2020). Many natural compounds and synthetic agents exhibit their anticancer effects through triggering autophagic cell death (Law et al, 2017;Xu et al, 2019;Kiruthiga et al, 2020;Pellerito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%